Implications of transition towards manufacturing on the environment: Saudi Arabia's Vision 2030 Context - Nasreen Alfantookh; Yousif Osman; Isam Ellaythey (Journal of Risk and Financial Management, 2023)
This study is based on the idea that Saudi Arabia's Vision 2030 considered the achievement of economic diversification is very crucial for the economy. In turn, this target requires a sustained increase in the contribution of the manufacturing sector in Gross Domestic Product (GDP). At the same time, the transition towards industrialization might trigger high rates of CO2 emissions, due to the escalated manufacturing demand for primary energy consumption (specifically fossil fuel). Ultimately, the high rates of CO2 emissions would have severe environmental consequences, such as environmental degradation. These environmental consequences might be more dangerous in a country extensively dependent on oil, such as Saudi Arabia. The study aims to investigate the manufacturing and environment nexus in an attempt to explore the validity of the inverted U-shaped curve, the so-called Kuznets hypothesis, during 1971-2021. Applying the econometric model autoregressive distributed lag (ARDL), the findings of the study do not show evidence supporting the validity of an inverted U-shaped Kuznets function in Saudi Arabia during the period of the study. Furthermore, the short-term results do not confirm the impact of increasing manufacturing on CO2 emissions. However, there are indications of positive effects, although limited, in the long-term.
Keywords: 650; ARDL; manufacturing; environmental Kuznets curve; Saudi Arabia’ s Vision 2030